Lessons from the rain forest: Experiences of the pilot program to conserve the Amazon and Atlantic forest of Brazil / Brent Millikan, Wiht Josef Leitmann, Judith Lisansky, Rebecca Abers, Martha Azevedo Irving, Olympio Barbanti Jr., Loretta Sprissler and Alice - Millikan, Brent [et.al]; 1. Leitmann, Josef\ 2. Lisansky, Judith\ 3. Abers, Rebecca\ 4. Azevedo Irving, Martha\ 5. BArbanti Jr., Olympio\ 6. Sprissler, Loretta\ 7. Guimaraes, Alice (Brasil: Brazil Rain Forest Unit)
The rain forests of brazil, about the pilot program, case studies, protection and management of indigenous lands and conservation units, developing an innovative approach to the protection of indigenous lands, extractive reserves, a model of community-based conservation and development, experimentation and demonstration, demonstration projects in environmental, protection and resource management, community mobilization for fire prevention and control, institutional strengthening for environmental management, promoting integrated environmental management in the amazon, a model for controlling deforestation on rural properties, science and technology, revitalizing research in science and technology, participation, lessons in the participation of civil society, next steps, towards a second phase of the pilot program.
Contents, llustrated cover, map
Col. Soc
Keywords: 1. GRUPOS RACIALES 2. RAIN FOREST 3. INDIGENISMO 4. SOCIOLOGÍA